Newly isolated strains of potentially microcystin-producing cyanobacteria in potable water: case study of Mawoni village, South Africa - Mutoti, Mulalo I.; Gumbo, Jabulani R.; Khwathisi, Adivhaho; Jideani, Afam I. O. (Frontiers in Environmental Science, 2024)
Toxic cyanobacterial species occur in aquatic ecosystems when favourable environmental conditions prevail. These bacteria can produce natural hepatotoxic metabolites called microcystins that can affect the quality of water. Human exposure to microcystins results from ingesting contaminated drinking water and therefore cyanobacterial species producing these toxins should be monitored in these waters. The present study aimed to trace and identify cyanobacterial strains that potentially produce microcystins in drinking water. To achieve this objective, advanced digital flow cytometry and polymerized chain reaction were used for the detection and identification of cyanobacterial strains in water samples collected from water storage containers in Mawoni village. Full-length 16S rRNA genes from cultured cyanobacteria were amplified and sequenced using the 16S primers. Three novel strains of Chroococcus sp. (m64187e-7881, m64187e-2143, and m64187e-0930) and two strains of Microcystis aeruginosa (m64187e-6729 and m64187e-1069) were detected and identified in drinking water samples. The presence of these strains could indicate the potential of microcystins occurrence in drinking water, which therefore, could present potential human health risk due to exposure to such cyanotoxins.